Sensitization of rat C6 glioma cells to ionizing radiation by porphyrins - RUTKOVSKIENĖ, Laimutė; PLĖŠNIENĖ, Laima; SENDIULIENĖ, Daiva; STANČIUS, Alfonsas; LIUTKEVIČIŪTĖ-NAVICKIENĖ, Jurgita (Acta medica Lituanica, 2011)
Background. Radiosensitizers are used in order to increase the efficacy of radiotherapy. Most of the presently known radiosensitizing agents have a poor selectivity and are not tumour-specific. Porphyrins have a selective uptake in tumour relative to the surrounding normal tissue. The aim of the present work was to test the capability of two photosensitizers – hematoporphyrin derivative (HpD) or temoporfin (mTHPC) – and gamma rays to produce some kind of selective inhibition of tumour cell proliferation. Materials and methods. Dark toxicity experiments were carried out using a sensitizer concentration range 0–50 μg/ml for HpD, or 0–5 μg/ml for mTHPC. For the radiosensitized treatment of rat C6 glioma cells, HpD was added at a final concentration of 1 μg/ml and mTHPC at a final concentration of 0.1 μg/ml. The irradiation with gamma rays was performed using doses ranging from 0 to 8 Gy. Cell survival was determined using the colony forming assay. Results. HpD (1 μg/ml) and mTHPC (0.1 μg/ml) were found to have no toxic effects on C6 glioma cells. A cytotoxic dose without drugs, inducing a reduction in colony survival by 20%, was achieved at 2 Gy and by 50% at 4 Gy. The radiosensitized treatment of cells with HpD resulted in a significant (p ≤ 0.05) decline in cell survival as compared with irradiation alone. For C6 treated with mTHPC, the results did not differ between the two groups (with and without the drug). Conclusions. The results of this study have shown that mTHPC (0.1 μg/ml) does not act as a radiosensitizer, whereas HpD can act, under certain conditions, as a tumour radiosensitizer. These findings suggest that HpD is a potential agent in combination with radiation therapy of malignant gliomas. Keywords: rat C6 glioma cells, radiosensitization, porphyrins, colony forming assay